Preparation and Characterization of DNA-Gold Nanocomposites for Metal ion Detection - Rana, Khyati (My University, 2014)
In present study, Gold nanoparticles of various sizes and shape has been synthesized and coupled with DNA to study the modification in the optical and electrokinetic behaviour. DNA does not show any absorbance in the visible region, but on binding with DNA, a red shift in gold nanoparticles (524 nm to 638 nm) has been observed. TEM shape and size analysis also prove the linking of DNA on Au nanostructures. Change in nanoparticle size distribution from 33 nm to 78 nm due to formation of nanocomposite was calculated through DLS. AFM studies help in correlating various 3D structures of Gold-DNA nanocomposites. Results have shown that fluorescence intensity of DNA increases on binding with gold nanospheres. Using this property, they are used as a low-cost sensing system which is simple and fast for detection of Mg+ ions. This sensing system has unprecedented sensitivity with a limit of detection from 20 ppm to 100 ppm for Mg+ ions. The fluorescence response of DNA-Gold nanoparticles is remarkably specific for Mg+ ions in the presence of other metal ions. This method of sensing is simple and easy to use just by mixing and incubation of the sample for 15 min at room temperature. It has successfully carried out the detection of Mg+ ions present in laboratory water and gelusil (an antacid). The DNA-Gold nanocomposite sensing system described here shows promising future potentials in the field of metal ion detection.
MT, DBTS
Keywords: DNA-Au nanospheres; Au nanorods; DNA-Au nanocomposite; Fluorescence; Metal ions; Mg2+ ions